Cascade stomach: a case report - Chhabra, Maninder Kaur; Mongia, Anil Kumar (International Surgery Journal, 2016)
Cascade stomach is an entity wherein there is biloculation of gastric cavity. The upper loculus is spherical in shape and the lower loculus is a narrow and tubular structure. Due to its morphological features, it is also known as “cup and spill stomach” or “champagne cup deformity”. Cascade stomach is well known to radiologists but its clinical spectrum is not well researched and there is much speculation about its pathological basis. There is limited data on the treatment of this condition in the literature. Treatment varying from psychiatric management and conservative measures to surgical intervention has been reported in individual case reports. We present a case of cascade stomach successfully treated with laparoscopic Nissen’s fundoplication along with the review of literature available on the subject.